Improving Listening Skills through Storytelling Methods for Students at Bustanul Athfal 'Aisyiyah Krakitan I Bayat Klaten - Herwandini (ETNOPEDAGOGI: Jurnal Pendidikan dan Kebudayaan, 2024)
The background of this research problem is the learning activities of listening skills that are less interesting for students at BA 'Aisyiyah Krakitan I Bayat Klaten, so that it affects children's skills in listening. Therefore, the researcher is interested in conducting research with the formulation of the problem: 1) how to use the storytelling method to improve listening skills in group A children at BA 'Aisyiyah Krakitan I Bayat Klaten?, 2) how to improve listening skills through the storytelling method in group A children at BA 'Aisyiyah Krakitan I Bayat Klaten? This study aims to determine the use of the storytelling method to improve listening skills in group A children at BA 'Aisyiyah Krakitan I Bayat Klaten and to determine the improvement of listening skills through the storytelling method. This research is a type of Classroom Action Research which is carried out in 2 cycles, each cycle consists of 2 meetings, each meeting consists of four components, namely planning, action, observation and reflection. The author conducted research on group A children aged 4-5 years totaling 14 children. This data collection method uses observation, interview, and documentation methods. The results of this study indicate that: 1) the use of storytelling methods to improve listening skills in group A children at BA 'Aisyiyah Krakitan I Bayat Klaten by: a) planning the storytelling method and writing it into the RPPH, b) determining the story theme, choosing a story theme according to the age of students (group A and group B), c) determining the media used, such as picture media, books, or hand puppets; 2) the improvement of listening skills through the storytelling method in group A children at BA 'Aisyiyah Krakitan I Bayat Klatena is 64.29%.